Activation of peripheral κ/δ opioid receptors mediates 15-deoxy-Δ12,14-prostaglandin J2 induced-antinociception in rat temporomandibular joint - Pena-Dos-Santos, Diego R.; Severino, Fernando P.; Lima Pereira, Sanívia Aparecida de; Rodrigues, Denise Bertulucci Rocha; Cunha, Fernando Queiroz; Manfredo Vieira, Silvio; Napimoga, Marcelo Henrique; Napimoga, Juliana Trindade Clemente (Neuroscience, 2009)
This study assessed the effect of the agonist 15d- PGJ2 administered into the rat temporomandibular joint (TMJ) on nociceptive behavioral and the anti-inflammatory potential of this prostaglandin on TMJ. It was observed that 15-deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) significantly reduced formalin-induced nociceptive behavior in a dose dependent manner, however injection of 15d-PGJ2 into the contralateral TMJ failed to reduce such effects. This antinociceptive effect is dependent on peroxisome proliferator-activated receptors-γ (PPAR-γ) since pre-treatment with GW9662 (PPAR-γ receptor antagonist) blocked the antinociceptive effect of 15d-PGJ2 in the TMJ. In addition, the antinociceptive effect of 15d-PGJ2 was also blocked by naloxone suggesting the involvement of peripheral opioids in the process. Confirming this hypothesis pre-treatment with κ, δ, but not μ receptor antagonists significantly reduced the antinociceptive effect of 15d-PGJ2 in the TMJ. Similarly to opioid agonists, the 15d-PGJ2 antinociceptive action depends on the nitric oxide (NO)/guanilate cyclase (cGMP)/ATP-sensitive potassium channel blocker(K+ATP) channel pathway since it was prevented by the pre-treatment with the inhibitors of nitric oxide synthase (NOS; aminoguanidine), cGMP (ODQ), or the K+ATP (glibenclamide). In addition, 15d-PGJ2 (100 ng/TMJ) inhibits 5-HT-induced TMJ hypernociception. Besides, TMJ treated with 15d-PGJ2 showed lower vascular permeability, assessed by Evan's Blue extravasation, and also lower neutrophil migration induced by carrageenan administration. Taken together, these results demonstrate that 15d-PGJ2 has a potential peripheral antinociceptive and anti-inflammatory effect in the TMJ via PPAR-γ activation. The results also suggest that 15d-PGJ2 induced-peripheral antinociceptive response in the TMJ is mediated by κ/δ opioid receptors by the activation of the intracellular L-arginine/NO/cGMP/K+ATP channel pathway. The pharmacological properties of the peripheral administration of 15d-PGJ2 highlight the potential use of this PPAR-γ agonist on TMJ inflammatory pain conditions. © 2009 IBRO.
Keywords: 15 Deoxy Delta12,14 Prostaglandin J2; 1h 1,2,4 Oxadiazolo[4,3 A]quinoxalin 1 One; 2 Chloro 5 Nitrobenzanilide; Adenosine Triphosphate Sensitive Potassium Channel; Aminoguanidine; Arginine; Delta Opiate Receptor; Glibenclamide; Guanylate Cyclase; Kappa Opiate Receptor; Naloxone; Nitric Oxide; Peroxisome Proliferator Activated Receptor Gamma; Potassium Channel Blocking Agent; 15 Deoxyprostaglandin J2; 15 Deoxyprostaglandin J2; Adenosine Triphosphate Sensitive Potassium Channel; Analgesic Agent; Cyclic Gmp; Delta Opiate Receptor; Drug Derivative; Formaldehyde; Kappa Opiate Receptor; Mu Opiate Receptor; Nitric Oxide Synthase; Peroxisome Proliferator Activated Receptor Gamma; Prostaglandin D2; Serotonin; Animals Cell; Animals Experiment; Animals Model; Antiinflammatory Activity; Antinociception; Blood Vessel Permeability; Cell Migration; Controlled Study; Drug Mechanism; Inhibition Kinetics; Male; Neutrophil; Nonhuman; Pharmacological Blocking; Priority Journal; Rat; Temporomandibular Joint Disorder; Animals; Chemically Induced Disorder; Dose Response; Drug Antagonism; Drug Effect; Inflammation; Metabolism; Pain; Signal Transduction; Temporomandibular Joint; Wistar Rat; Analgesics; Animal; Cyclic Gmp; Dose-response Relationship, Drug; Formaldehyde; Inflammation; Katp Channels; Male; Nitric Oxide Synthase; Pain; Ppar Gamma; Prostaglandin D2; Rats; Rats, Wistar; Receptors, Opioid, Delta; Receptors, Opioid, Kappa; Receptors, Opioid, Mu; Serotonin; Signal Transduction; Temporomandibular Joint